Assessment of birth preparedness and complication readiness among pregnant women in rural area of Chhattisgarh: a community based cross-sectional study - Deshmukh, Namita; Borkar, Avinash; Rathore, Mrityunjay (International Journal Of Community Medicine And Public Health, 2019)
Background: Neonatal and maternal mortality are the major concerns in the country mainly due to the “three delays” in seeking, reaching, and obtaining appropriate care. Birth preparedness and complication readiness (BPACR) is one of the most important tools to assess these delays. BPACR is the process of planning for normal birth and anticipating the actions needed in case of an emergency. The current study was undertaken to assess the status of BPACR among pregnant women in rural area of Kharsiya block in Raigarh district. Methods: A community-based, cross-sectional study was conducted among 110 pregnant women in rural area of Kharsiya during January-June 2017. All the pregnant females were interviewed using a pretested and structured questionnaire. Knowledge about danger signs, planning for transport, place and delivery by skilled birth attendant, financial management were assessed. BPACR index was also calculated. Results: The BPACR index was found to be very low (27.79%). About 73.65% women identified a skilled birth attendant for delivery but, only 10% women saved money and only 2.7% women had identified a blood donor for emergency. Nearly 74.54% women had no knowledge about danger or warning signs during pregnancy while 89.09% were unaware of complications during labour and 97.27% women did not know about puerperal complications. Conclusions: BPACR index in this rural area was very low. Vast majority of women were not knowledgeable about birth preparedness and complication readiness.